2012
DOI: 10.4028/www.scientific.net/ddf.331.181
|View full text |Cite
|
Sign up to set email alerts
|

Defect Behaviour in Yttria-Stabilised Zirconia Nanomaterials Studied by Positron Annihilation Techniques

Abstract: Recent experimental and theoretical investigations on a variety of yttria-stabilised zirconia (YSZ) nanomaterials are reviewed. The investigations were conducted within the frame of a collaboration of three institutions: (i) Charles University in Prague, (ii) Helmholtz Centre Dresden-Rossendorf and (iii) Donetsk Institute for Physics and Engineering of the NAS of Ukraine, Materials studied involved pressure-compacted nanopowders of binary and ternary (with Cr2O3 additive) YSZ and YSZ ceramics obtained by sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…. Note that two o‐Ps components were detected in the YSZ nanopowder: a dominating long‐lived component with lifetime 20–30 ns and a weak component with lifetime 1–2 ns, see Refs . for details.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Note that two o‐Ps components were detected in the YSZ nanopowder: a dominating long‐lived component with lifetime 20–30 ns and a weak component with lifetime 1–2 ns, see Refs . for details.…”
Section: Resultsmentioning
confidence: 99%
“…Positron annihilation spectroscopy (PAS) is a well‐recognized tool of microstructure investigation on solids containing open‐volume defects . During past few years, PAS was utilized in studies covering the pure ZrO 2 , the binary YSZ as well as the ternary oxide solid solution YSZ + chromia (YSZ‐Cr) nanomaterials. This study represents an extension of this research toward the binary MgSZ and CeSZ nanopowders containing stabilizers with metal cation valences of 2+ (Mg) and 4+ (Ce), that is, valences different from those of Y or Cr (3+).…”
Section: Introductionmentioning
confidence: 99%
“…150 For instance, PAS has been used for estimating the mean grain size from conventional positron lifetime technique 151 and displaying trends in microstructure evolution which take place during sintering of YSZ ceramics at different temperatures. 152 Earlier studies on the control of grain growth during sintering of YSZ have also shown that a transient stage of abnormal grain growth, which is determined by the microstructural situation after compaction, occurs in the non-isothermal temperature range, between 1100 and 1200uC. 142 In order to maintain the nanocrystalline nature of YSZ ceramics produced from nanograined powders, the stage of abnormal grain growth should be kept as short as possible.…”
Section: Densification and Grain Growthmentioning
confidence: 99%
“…150 For instance, PAS has been used for estimating the mean grain size from conventional positron lifetime technique 151 and displaying trends in microstructure evolution which take place during sintering of YSZ ceramics at different temperatures. 152…”
Section: Microstructural Development In Ysz Nanoceramicsmentioning
confidence: 99%
“…The study represents an extension of our recent research on yttria-stabilised zirconia (YSZ) nanomaterials reviewed in [4]. To authors' knowledge, no positron annihilation studies of the zirconia nanosystems doped with RE 2 O 3 were reported before in the published literature.…”
Section: Introductionmentioning
confidence: 99%